Simple criterion for predicting fatigue life under combined bending and torsion loading - K. Slámecka; J. Pokluda (Fracture and Structural Integrity)
Multiaxial fatigue is a challenging problem and, consequently, a number of methods has been developed to aid in design of components and assemblies. Following the complexity of the problem, these approaches are often elaborate and it is difficult to use them for simple loading cases. In this paper, an empirical approach for constant amplitude, proportional axial and torsion loading is introduced to serve as a basic engineering tool for estimating fatigue life of rotational structural parts. The criterion relies on a quadratic equivalent-stress formula and requires one constant parameter to be determined from experiments. The comparison with similar classical stressbased approaches using data on diverse materials (several steels, aluminium alloy, and nickel base superalloy) reveals very good agreement with experimental data.